Case report: Proton pump inhibitor drug-related problem in pancreatic cancer patient unmasks pancreatic enzyme insufficiency. (March 2022) - Giani, Jasmine; Chambers, Carole R; Sawyer, Michael B
Introduction: Palliative care aims to improve the quality of life of patients with a life-limiting or life-threatening illness and is multifaceted involving comprehensive interdisciplinary assessments and interventions. Interdisciplinary palliative care in the setting of untreatable cancer diagnoses is of particular importance due to additional considerations that must be taken as patients are often undergoing palliative chemotherapy and/or radiation therapy. These patients' complexity warrants special considerations and attentiveness to drug-related problems. Case report: The purpose of this case report is to highlight the importance of both complete and comprehensive medication histories in cancer care and the impact of proton pump inhibitors on pancreatic enzyme insufficiencies secondary to pancreatic cancers. This case involves a drug-related problem involving three medications that are commonly used in pancreatic cancer patients: pancreatic enzyme replacement therapy, a proton pump inhibitor, and a fluoroquinolone antibiotic. The patient presented in this case report is an 80-year-old man diagnosed with unresectable pancreatic cancer with a history of symptomatic gastroesophageal reflux disease managed with a proton pump inhibitor, specifically tablets of the 40 mg strength of pantoprazole magnesium taken orally once daily. During the patient's first of five 28-day cycles of palliative-intent chemotherapy with gemcitabine and nab -paclitaxel, the patient presented to the emergency department due to fever and, although not severely neutropenic, was prescribed amoxicillin/clavulanate and ciprofloxacin due to his advanced age. After reading a patient advisory on a ciprofloxacin patient information sheet that advised avoidance of concomitant administration of ciprofloxacin and magnesium, the patient self-discontinued his pantoprazole as it was a magnesium salt formulation. This discontinuation was followed by two weeks of persistent foul-smelling diarrhea, flatulence, and abdominal pain. Management and outcome: The patient's healthcare team symptomatically managed the patient with oral and intravenous rehydration unaware of the cause of the symptoms. A trial of pancreatic enzyme replacement therapy was initiated; however, it was unsuccessful in resolving his symptoms. After further investigation and a more in-depth patient interview, it was discovered that the discontinued proton pump inhibitor was likely the cause of the patient's new symptoms and was subsequently re-initiated. Pancreatic enzyme replacement therapy in combination with re-initiation of pantoprazole therapy essentially resolved all symptoms. Discussion: Before his diagnosis of unresectable pancreatic cancer, the patient had been on proton pump inhibitor therapy for nearly a decade. He had significant atrophy of the pancreas and an undoubtedly decreased pancreatic enzyme and bicarbonate production; however, he did not experience foul-smelling diarrhea indicative of pancreatic enzyme insufficiency while he was on his proton pump inhibitor. We believe that with his proton pump inhibitor therapy, he was unknowingly being partially treated for his worsening pancreatic enzyme insufficiency, specifically the component related to his lack of bicarbonate production and secretion. His discontinuation of his proton pump inhibitor led to a decrease in gastric acid, small bowel, and normal intraduodenal pH, which resulted in any remaining pancreatic enzyme reserve to become non-functional, unmasking his pancreatic enzyme insufficiency. An initial empiric trial of pancreatic enzyme replacement therapy failed in the absence of a proton pump inhibitor; however, within days of restarting his proton pump inhibitor along with pancreatic enzyme replacement therapy, his gastrointestinal symptoms completely resolved. This is due to the decrease of gastric and intraduodenal acidity, which better enabled the function of pancreatic enzymes present in pancreatic enzyme replacement therapy.